Nilai-Nilai Tradisi Bukoba di Pasir Pengaraian Rokan Hulu Provinsi Riau - Syefriani Syefriani; Yahyar Erawati; Defriansyah Defriansyah (Universitas Gadjah Mada, 2021)
Bukoba Tradition is an oral tradition that delivers news in the form of verse, and the verse contains words and meanings to be conveyed accompanied by music. Bukoba is a tradition that contains values which should be recognized by the younger generation. Bukoba contains educational, religious, social, and traditional values. Educational value is an invitation to listeners to preserve customs, culture and tradition which had been long gone. Religion value is in the form of conveying to the audience for always carrying out acts of worship and never forgetting Allah SWT. Social Value is when the audience can meet their relatives and old friends who haven't seen them for a long time. Traditional value is a medium to inherit traditional values. Introduction to values in Bukoba must be instilled to the younger generation of Rokan Hulu so that they can be nurtured and not eroded by globalization.Keywords: Bukoba, Values, Oral Tradition